2022
DOI: 10.3389/fgene.2022.951893
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the causality between ankylosing spondylitis and atrial fibrillation: A two-sample Mendelian randomization study

Abstract: Objective: To study whether ankylosing spondylitis (AS) has a causal effect on the risk of atrial fibrillation (AF) using two-sample Mendelian randomization (MR) analysis.Methods: Single nucleotide polymorphisms (SNPs) were selected as independent instrumental variables (IVs) from a GWAS study of AS. Summary data from a large-scale GWAS meta-analysis of AF was utilized as the outcome dataset. Inverse-variance weighted (IVW) model was used for the primary analysis. Multiple sensitivity and heterogeneity tests w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Finally, AS has been associated with cardiovascular risk factors such as diabetes ( Chen et al, 2014 ; Chou et al, 2014 ), hypertension ( Chen et al, 2014 ; Chou et al, 2014 ), dyslipidemia ( Chen et al, 2014 ; So et al, 2017 ), obesity ( Catapano et al, 2016 ), and metabolic syndrome ( Haroon et al, 2014 ), which interact with AS and affect the occurrence of CVD complications in AS patients. Our MR analysis did not provide evidence for a causal effect of AS on AF, MI, Coronary atherosclerosis, Ischemic stroke, and VHD, which is consistent with previous MR study results ( Chen et al, 2022 ; Mei et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, AS has been associated with cardiovascular risk factors such as diabetes ( Chen et al, 2014 ; Chou et al, 2014 ), hypertension ( Chen et al, 2014 ; Chou et al, 2014 ), dyslipidemia ( Chen et al, 2014 ; So et al, 2017 ), obesity ( Catapano et al, 2016 ), and metabolic syndrome ( Haroon et al, 2014 ), which interact with AS and affect the occurrence of CVD complications in AS patients. Our MR analysis did not provide evidence for a causal effect of AS on AF, MI, Coronary atherosclerosis, Ischemic stroke, and VHD, which is consistent with previous MR study results ( Chen et al, 2022 ; Mei et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…The applicability of MR studies has been demonstrated in the evaluation of diverse causal relationships between behavioral exposures, educational attainment, socioeconomic statuses, and various diseases ( Tillmann et al, 2017 ; Harrison et al, 2020 ). Furthermore, prior MR explorations have scrutinized the causal implications of AS on stroke ( Mei et al, 2022 ) and atrial fibrillation ( Chen et al, 2022 ). Nonetheless, these endeavors have largely focused on specific forms of CVDs.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, AS has been associated with cardiovascular risk factors such as diabetes (Chen et al, 2014;Chou et al, 2014), hypertension (Chen et al, 2014;Chou et al, 2014), dyslipidemia (Chen et al, 2014;So et al, 2017), obesity (Catapano et al, 2016), and metabolic syndrome (Haroon et al, 2014), which interact with AS and affect the occurrence of CVD complications in AS patients. Our MR analysis did not provide evidence for a causal effect of AS on AF, MI, Coronary atherosclerosis, Ischemic stroke, and VHD, which is consistent with previous MR study results (Chen et al, 2022;Mei et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…At the outset of the research design, single nucleotide polymorphisms (SNPs) ( P < 5 × 10 -5 ) that are strongly related with exposure were selected as IVs. We only used independent SNPs with r 2 < 0.01 within a distance of 5,000 kb in order to remove the chain disequilibrium (LD) bias ( 21 ). Therefore, the default parameters of the TwoSampleMR package in R (physical distance threshold, 5,000 kb, r 2 < 0.01) were set for aggregating the data and clipping possible LD genetic variation.…”
Section: Methodsmentioning
confidence: 99%